The Strength of Notarial Deed Proof as Evidence in the Civil Court Process - Demak, Astri Angreani Kiyai (TABELLIUS: Journal of Law, 2024)
The judiciary has a very important position and role in accepting, adjudicating and deciding every case submitted to it. When deciding a civil case, the court must pay attention to the evidence presented by the parties. An authentic notary deed is perfect evidence and can be used as evidence in court. The aim of this research is to determine and analyze the evidentiary strength of notarial deeds canceled by the Court in the civil justice process, as well as to determine and analyze the responsibilities of notaries as public officials due to the cancellation of deeds by the Court. The method used by researchers is normative juridical with a statutory approach. The specifications of this research are prescriptive. The type of data used is secondary data sourced from materials obtained from literature studies. Based on the results of the research, 1) a Notarial Deed is an authentic deed, where as written evidence it has a high position in evidence, that is, it has perfect evidentiary power and is binding like a judge's decision. So there is no need to create or supplement other evidence. If a party denies it, that party must prove their statement in accordance with applicable legal regulations. If it can be proven in a court that one or all of the evidence is external, formal or material, the evidentiary strength of the notarial deed is degraded as a private deed. 2) The notary as an official who has the authority to make authentic deeds is fully responsible if the deed he makes is detrimental to clients/people using notary services. In the event that a Notary's deed is annulled by a judge's decision in court, then if it causes losses to interested parties, the Notary can be required to provide compensation, as long as this occurs due to the Notary's fault. The Law on Notary Positions (UUJN) has determined that only notarial deeds that are proven to have degraded in evidentiary value as private deeds can be subject to civil sanctions. For notarial deeds that are cancelled, notarial deeds that can be cancelled, notarial deeds that are null and void by law, notarial deeds that do not have binding legal force and invalid notarial deeds, there are no sanctions whatsoever against the Notary.